'A Place of Our Own': Puerto Rican Muslims and Their Architectural Responses as Quadruple Minorities. (1st July 2022) - Chitwood, Ken
This article adopts a horizontally integrative approach to understanding Islamic architecture in the traditionally excluded geography of Puerto Rico. Puerto Rico is literally and figuratively left off the map of the so-called 'Muslim world' and there is very little about its mezquitas (mosques) or the Andalusian legacy in its built environment in the published record of Islamic architectures, sites, and responses. I argue, based on my ethnographic fieldwork undertaken in 2015‐17 and 2019‐21, that Puerto Rican Muslims counter their multiple marginalizations ‐ identifying as Muslim in the Puerto Rican community, Puerto Rican in the Muslim community, and both Muslim and Puerto Rican in the context of the American empire ‐ through various architectural responses. To make this argument, I discuss the physical landscape of Islamic architecture in Puerto Rico, including innovative and adaptive spaces constructed in protest of the elitism found in certain mezquitas, and locales where Andalusian architectural influence is readily visible. This leads to my critical examination of how the diverse, dynamic, and vernacular architectural responses of Puerto Rican Muslims speak to each of their minoritizations.